Pengaruh Penggunaan Media Wordwall Terhadap Minat Belajar Peserta Didik Pada Mata Pelajaran Aqidah Akhlak Kelas VII di MTsN 6 Kota Padang - Tiara Salsabila; M Basyiruddin; Azrul Azrul (Journal of Pedagogy and Online Learning, 2023)
The purpose of this study was to determine the learning interest of students before using Wordwall media in Aqidah Akhlak Class VII subjects at MTsN 6 Padang City, to determine the learning interest of students after using Wordwall media in Aqidah Akhlak Class VII subjects at MTsN 6 Padang City, and to determine the effect of using Wordwall media in Aqidah Akhlak subjects on the learning interest of class VII students at MTsN 6 Padang City. This research is quantitative research using experimental. The population in this study were all seventh grade students at MTsN 6 Padang City in 2022/2023 even semester. Sampling in this study was purposive sampling technique, the class selected as the experimental class was class VII. 7 and control class VII. 10. The results showed that the results of hypothesis testing with SPSS version 26 or sig (2-tailed) were obtained = 0.009, it can be concluded that (0.009 <0.05), which means Ho is rejected and Ha is accepted. And T count> T table is 2.770> 1.675 which means Ho is rejected and Ha is accepted, stating that there is an effect of using Wordwall media on students' interest in learning Aqidah Akhlak class VII subjects at MTsN 6 Padang City. It can be seen that the learning interest of students who use Wordwall media is better than the learning interest of students who do not use Wordwall learning media or other media.